Corporate Performance on Science and Technology Innovation of Chinese High-Tech Listed Companies - Wang, Chunqing; Na Srito, Pavinee; Jongwiriyajaroenchai, Arphaporn (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
This research article aims to: 1) examine the factors impact on enterprise performance, 2) study the mediating role intermediate mechanism of science and technology innovation impact between management firm’s ability and enterprise performance of high-tech enterprises. In order to achieve this objective. This research was quantitative research, collected data from Chinese high-tech listed companies’ employees of 397 respondents. They were selected by simple random sampling, the instrument for collecting data was a questionnaire with a content validity (IOC) of .813 and a reliability value of Cronbach’s alpha coefficient of .916. Analysis of data via SEM by AMOS. The research result was found as follow: Capacities in managing positively impact on enterprise performance, scientific and technology innovation. Learning oriented approach to tax relief administration positively impact on scientific and technology innovation. Management support impact on scientific and technology innovation. And scientific and technology innovation impact on enterprise performance.2) the mechanism of science and technology innovation Play mediating role impact between management firm’s ability and enterprise performance of high-tech enterprises. These results of the study are having various theoretical, practical and policy making implications as discussed by the author